Policies for sustainable land management in the East African Highlands: Summary of papers and proceedings of the conference held at the United Nations Economic Commission for Africa. Addis Ababa, Ethiopia. 24-26 April 2002 - Benin, Samuel; Pender, John L.; Ehui, Simeon K. (International Food Policy Research Institute, 2002)
This document presents the proceedings of the international conference held at the United Nations Economic Commission for Africa, Addis Ababa, Ethiopia, April 24-26, 2002. The theme of the conference was Policies for Sustainable Land Management in the East African Highlands, which was convened to bring together researchers, policy makers, development practitioners, donors and others to review, discuss and synthesize the findings and policy implications of policy research related to sustainable land management in the East African highlands. The conference also aimed at increasing awareness of policy makers and other stakeholders of the impacts of policies, programs and other factors on land management, agricultural productivity, poverty and food security; to discuss promising strategies to promote more sustainable land management, increased agricultural productivity, and reduced poverty and food insecurity; and to consider priorities for policy action and future research.